Oil extraction from spent coffee grounds (SCG) using soxhlet extraction method employing hexane as solvent / A’isyatul Damia Ahmad Sadli@Ahmad Fadli - Ahmad Sadli@Ahmad Fadli, A’isyatul Damia (2023)
Coffee is the most popular beverage worldwide, with its regular consumption increasing. The production of coffee as a drink generates an average of 6 million tons of spent coffee grounds (SCG) per year globally. These yearly wastes are often burned, combined with animal feed, or dumped in landfills in bulk. Due to their high content of tannins and caffeine, coffee wastes can degrade soil quality and induce carcinogenicity when mixed with animal fodder. The nature of SCGs allows for a wide range of uses. Therefore, several studies have been conducted on how to turn them into valuable products. SCG could be helpful as a promising source of antioxidative materials and it principally consists of lignin, cellulose, and hemicellulose and various bioactive molecules . In this study, the experiments of oil extraction from spent coffee ground SCG) employing hexane as solvent were conducted. The method involved in this research was Soxhlet Extraction (SE). Under the ideal circumstances of a four-cycle SE, the DSCG may generate around 14.03 wt% oil. To establish the best method for extracting oil and the amount of free fatty acids (FFA) in the oil, the extracted coffee oil from up to seven sequential extractions was examined using Fourier Transform Infrared Spectroscopy (FTIR). The findings revealed similarities between the information gained from earlier studies. This study aimed to identify the optimum percentage of oil from extracted dried SCG that involved the drying process of spent coffee grounds (SCG), extraction process using Soxhlet Extractor, and separation process via the rotary evaporator.